2012
DOI: 10.1371/annotation/8580b50a-1556-4c86-aeb6-a88af839297a
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Enhancer of Zeste Homolog 2 Induces Pulmonary Artery Smooth Muscle Cell Proliferation

Abstract: Introduction: Pulmonary Arterial Hypertension (PAH) is a progressively devastating disease characterized by excessive proliferation of the Pulmonary Arterial Smooth Muscle Cells (PASMCs). Studies suggest that PAH and cancers share an apoptosis-resistant state featuring excessive cell proliferation. The proliferation of cancer cells is mediated by increased expression of Enhancer of Zeste Homolog 2 (EZH2), a mammalian histone methyltransferase that contributes to the epigenetic silencing of target genes. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Several cancer cell lines proliferate when EZH2 is overexpressed, whereas tumor growth is inhibited by EZH2 suppression. Surprisingly, EZH2 has been demonstrated to prevent the progression of PAH by preventing hPASMC migration and proliferation [21,99]. The potential benefits of EZH2 inhibitors as cancer therapies are highlighted by the fact that inhibiting EZH2 decreases the proliferation of numerous cancer cell lines [100].…”
Section: Comparison Of Sin3a's Effects On Cancer and Its Implications...mentioning
confidence: 99%
“…Several cancer cell lines proliferate when EZH2 is overexpressed, whereas tumor growth is inhibited by EZH2 suppression. Surprisingly, EZH2 has been demonstrated to prevent the progression of PAH by preventing hPASMC migration and proliferation [21,99]. The potential benefits of EZH2 inhibitors as cancer therapies are highlighted by the fact that inhibiting EZH2 decreases the proliferation of numerous cancer cell lines [100].…”
Section: Comparison Of Sin3a's Effects On Cancer and Its Implications...mentioning
confidence: 99%
“…Accordingly, inhibition of G9a by its inhibitor BIX-01294 decreased the migration, proliferation, and contractility of fetal PASMCs in relation to a significantly increased global methylation level in the fetal PASMCs [ 106 ]. The expression level of the enhancer of zeste homolog 2 (EZH2) is increased in PASMCs isolated from PAH animals, leading to enhanced hypertrophy, right-ventricle systolic pressure, and PAH development [ 107 ]. Similarly, the upregulation of EZH2 in human PASMCs increases migration and proliferation, as well as reduces apoptosis [ 107 ].…”
Section: Epigenetic Mechanisms Of Pathogenesis In Pahmentioning
confidence: 99%
“…The expression level of the enhancer of zeste homolog 2 (EZH2) is increased in PASMCs isolated from PAH animals, leading to enhanced hypertrophy, right-ventricle systolic pressure, and PAH development [ 107 ]. Similarly, the upregulation of EZH2 in human PASMCs increases migration and proliferation, as well as reduces apoptosis [ 107 ]. Shi et al identified that pharmacologic suppression of EZH2 with EPZ005687 improves transverse aortic constriction (TAC)-induced PAH by blocking ROS generation in the pulmonary system [ 108 ].…”
Section: Epigenetic Mechanisms Of Pathogenesis In Pahmentioning
confidence: 99%
“…Also, a reduction of the mitochondria-localized deacetylase sirtuin 3 gene ( SIRT3 ) expression suppresses mitochondrial function, inhibits apoptosis, and activates several pulmonary hypertension-related transcription factors [124]. Besides, increased expression of a histone methyltransferase, the enhancer of zeste homologue 2, is found in proliferating PASMCs and associated with the progression of PH [125].…”
Section: The Epigenetics Of Ph-lhdmentioning
confidence: 99%